Intervenciones de enfermería durante la atención a las trabajadoras sexuales. Centro de Salud Cordero Crespo. Octubre 2023 – febrero 2024. - Rivadeneira Gatia, Johanna Maribel (2024)
The present research work Nursing interventions during the care of sex workers. Cordero Crespo Health Center October 2023 – February 2024, had as its main objective to determine the nursing interventions that should be carried out during the stay of sex workers at the Cordero Crespo Health Center, for which a methodology of a quantitative study was applied, of a descriptive type of cross-sectional nature. The study was carried out with a population of 20 sex workers who come to the health center. To obtain data, an assessment guide was developed under the Madeleine Leininger model, which was able to identify the problems presented by sex workers, subsequently the nursing interventions that should be carried out respectively to each problem were obtained as a result. In addition, a guide to nursing interventions was prepared in which the activities and plans of talks on health issues that were developed are indicated. As a result, a good capture of information by sex workers was obtained, which was given through adequate education and promoting health practices ;KEY WORDS: SEX WORKERS, NURSING INTERVENTIONS, COMPREHENSIVE CARE, MADELEINE LEININGER.